2015
DOI: 10.1002/ange.201506311
|View full text |Cite
|
Sign up to set email alerts
|

Ribosome Subunit Stapling for Orthogonal Translation in E.coli

Abstract: The creation of orthogonal large and small ribosomal subunits, which interact with each other but not with endogenous ribosomal subunits, would extend our capacity to create new functions in the ribosome by making the large subunit evolvable. To this end, we rationally designed a ribosomal RNA that covalently links the ribosome subunits via an RNA staple. The stapled ribosome is directed to an orthogonal mRNA, allowing the introduction of mutations into the large subunit that reduce orthogonal translation, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 19 publications
(9 reference statements)
0
9
0
Order By: Relevance
“…These structural differences may confer different biological properties to the circularly permuted molecular species. Circular permutation has been used as a method to study various properties of RNA molecules, e.g., the order of folding ( Pan, 2000 ; Lease et al, 2007 ), including the folding ( Kitahara and Suzuki, 2009 ) or tethering of rRNA ( Fried et al, 2015 ; Orelle et al, 2015 ) and to make molecular tools, e.g., permuted group I introns as vehicles for producing circularized exons ( Puttaraju and Been, 1992 ; Ford and Ares, 1994 ) or permuted rRNA in a protocol for the incorporation of non-natural nucleoside analogs ( Erlacher et al, 2011 ). In nature, circular permuted RNAs can be produced by RNA processing or by genomic rearrangement.…”
Section: Introductionmentioning
confidence: 99%
“…These structural differences may confer different biological properties to the circularly permuted molecular species. Circular permutation has been used as a method to study various properties of RNA molecules, e.g., the order of folding ( Pan, 2000 ; Lease et al, 2007 ), including the folding ( Kitahara and Suzuki, 2009 ) or tethering of rRNA ( Fried et al, 2015 ; Orelle et al, 2015 ) and to make molecular tools, e.g., permuted group I introns as vehicles for producing circularized exons ( Puttaraju and Been, 1992 ; Ford and Ares, 1994 ) or permuted rRNA in a protocol for the incorporation of non-natural nucleoside analogs ( Erlacher et al, 2011 ). In nature, circular permuted RNAs can be produced by RNA processing or by genomic rearrangement.…”
Section: Introductionmentioning
confidence: 99%
“…Selectively directing a new 23S rRNA to an orthogonal mRNA, by controlling the association between the orthogonal 16S rRNAs and 23S rRNAs, would enable the evolution of new function in the large subunit. Previous work covalently linked orthogonal 16S rRNA and a circularly permuted 23S rRNA to create orthogonal ribosomes with low activity5,6; however, the linked subunits in these ribosomes do not associate specifically with each other, and mediate translation by associating with endogenous subunits. Here we discover engineered orthogonal ‘stapled’ ribosomes (with subunits linked through an optimized RNA staple) with activities comparable to that of the parent orthogonal ribosome; they minimize association with endogenous subunits and mediate translation of orthogonal mRNAs through the association of stapled subunits.…”
mentioning
confidence: 99%
“…Ribosomal subunits can be covalently linked by joining helix 44 of the 16S rRNA to Helix 101 of a circularly permuted 23S rRNA (Fig. 1) 5,6,10 through either a flexible tether, the A 8/9 tether, or the hinge from the J5-J5a region from the Tetrahymena group I self-splicing intron11; the latter strategy created the parental orthogonal ‘stapled’ ribosome (herein called O-d0d0). These O-ribosomes with linked subunits maintain only 30% of the activity of the parental O-ribosome (Fig.…”
mentioning
confidence: 99%
“…It has been suggested that the mutual mobility of the two ribosomal subunits is essential for the translocation mechanism. However, a functional ribosome with covalently linked subunits has been successfully created independently by two groups 1,19 , calling this hypothesis into question, or suggesting that the covalently linked structure retained some mobility.…”
Section: Discussionmentioning
confidence: 99%